2016
DOI: 10.2147/ijn.s96558
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and performance evaluation of multilayered photoanodes by introducing mesoporous carbon and TiO<sub>2</sub> for humic acid adsorption

Abstract: Nanostructured photoanodes were prepared via a novel combination of titanium dioxide (TiO 2 ) nanoparticles and mesoporous carbon (C). Four different photoanodes were synthesized by sol–gel spin coating onto a glassy substrate of fluorine-doped tin oxide. The photocatalytic activities of TiO 2 , TiO 2 /C/TiO 2 , TiO 2 /C/C/TiO 2 , and TiO 2 /C/TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Also, when compared with mesoporous carbon and TiO 2 from another study, the findings of this study showed a significant surface roughness that differed as wt.% increased, while the surface of TiO 2 showed a small degree of homogenous roughness and likewise the mesoporous carbon. AFM results demonstrated the effect of mesoporous PSA on the surface roughness of PSA@TiO 2 /PS (Hosseini et al 2016). However, based on the image statistics in Table 2 on average roughness (R a ) the 2.5 wt.% had the highest surface roughness of 4.62 nm at 2.5 wt.%.…”
Section: Morphology Of Photocatalystmentioning
confidence: 94%
“…Also, when compared with mesoporous carbon and TiO 2 from another study, the findings of this study showed a significant surface roughness that differed as wt.% increased, while the surface of TiO 2 showed a small degree of homogenous roughness and likewise the mesoporous carbon. AFM results demonstrated the effect of mesoporous PSA on the surface roughness of PSA@TiO 2 /PS (Hosseini et al 2016). However, based on the image statistics in Table 2 on average roughness (R a ) the 2.5 wt.% had the highest surface roughness of 4.62 nm at 2.5 wt.%.…”
Section: Morphology Of Photocatalystmentioning
confidence: 94%